Experimental ocean acidification and food limitation reveals altered energy budgets and synergistic effects on mortality of larvae of a coastal fish - Siegfried, Emma; Johnson, Darren W. (Frontiers in Marine Science, 2023)
Ocean acidification (OA) presents a unique challenge to early life stages of marine species. Developing organisms must balance the need to grow rapidly with the energetic demands of maintaining homeostasis. The small sizes of early life stages can make them highly sensitive to changes in environmental CO2 levels, but studies have found wide variation in responses to OA. Thus far most OA studies have manipulated CO2 only, and modifying factors need to be considered in greater detail. We investigated the effects of high pCO2 and food ration on rates of growth and mortality of a coastal fish, the California Grunion (Leuresthes tenuis). We also examined how CO2 and food levels affected feeding success, metabolic rate, and swimming activityprocesses reflective of energy acquisition and expenditure. In general, exposure to high CO2 decreased energy intake by reducing feeding success, and increased energy expenditure by increasing metabolic rate and routine swimming speed, though the magnitudes of these effects varied somewhat with age. Despite these changes in energetics, growth of biomass was not affected significantly by pCO2 level but was reduced by low ration level, and we did not detect an interactive effect of food ration and pCO2 on growth. However, under OA conditions, larvae were in poorer condition (as evaluated by the mass to length ratio) by the end of the experiment and our analysis of mortality revealed a significant interaction in which the effects of OA were more lethal when food energy was limited. These results are consistent with the idea that although energy can be reallocated to preserve biomass growth, increased energetic demand under ocean acidification may draw energy away from maintenance, including those processes that foster homeostasis during development. Overall, these results highlight both the need to consider the availability of food energy as a force governing species' responses to ocean acidification and the need to explicitly consider the energy allocated to both growth and maintenance as climate changes. This is a provisional file, not the final typeset article demonstrated harmful effects of ocean acidification on a variety of species (